(untitled) (Physical Education, Health and Social Sciences, 2025)
This qualitative study explores university educators’ preferences for specific pedagogical approaches and their underlying beliefs, motivations, and challenges. Using semi-structured interviews with twelve educators from diverse institutional backgrounds, the research uncovers how teaching preferences are shaped by experiential, cognitive, and contextual factors. Thematic analysis revealed that while lectures remain widely used, many educators favor interactive and student-centered strategies such as hands-on learning, cross-questioning, feedback loops, and case-based instruction. Motivations for these preferences included the desire to foster critical thinking, improve comprehension, and enhance student satisfaction. Educators’ beliefs reflected confidence in the transferability of global pedagogies and the importance of tailoring instruction to diverse learners. However, significant challenges—such as lack of resources, large class sizes, technological barriers, and institutional resistance—were also reported. The findings highlight the need for pedagogical development initiatives that are aligned with educators’ lived experiences and support both innovation and instructional autonomy.